Desarrollo embrionario-larval del pez tropical Hemirhamphus brasiliensis(Beloniformes: Hemirhamphidae) a partir de huevos recolectados del medio natural - Rosas, Jesús (2008)
The embryo formation and larval development of Hemirhamphusbrasiliensis Linnaeus, 1758 (Pisces: Hemirhamphidae) is described from morula stage eggs col-lected on Sargassum sp. Thalii in the field (10°50’55.2” N y 64°09’467” W). The eggs were spherical, 1 923.54 ±72.35 μm diameter with several corionic filaments, and are striated. During the first 48 h the embryo developed cephalic vesicle, miomers, and a heart located on the external body surface, beating strongly and circulating colorless blood which became pigmented red later. Before hatching, the larva developed kidney, gut tract, liver and biliar vesicle, pectoral fins, four pairs of gill arches and the mouth. The larva hatched at 114 h, the body was torpedo-shaped, yellow-green, with several dendriform melanophores; the pelvic fin was observed 72 h post hatching. At 240 hours the metamorphoses was completed. When the larvae hatched they could ingest Artemiametanauplii.